New Alkaloids from Pancratium maritimum - Ibrahim, Sabrin R. M.; Mohamed, Gamal A.; Shaala, Lamiaa A.; Youssef, Diaa T. A.; El Sayed, Khalid A. (Planta Medica, 2013)
As a part of ongoing search efforts for the discovery of anticancer lead entities from natural sources, bulbs and flowers of the amaryllidaceous plant Pancratium maritimum have been investigated. Fractionation of the extracts of the fresh flowers and bulbs of P. maritimum led to the isolation of four new alkaloids, namely pancrimatines A (1) and B (2), norismine (3), and pancrimatine C (4), together with the previously reported N-methyl-8,9-methylenedioxy-6-phenanthridone (5), trispheridine (6), and N-methyl-8,9-methylenedioxyphenanthridine (7). The structures of these alkaloids were established on the basis of extensive 1D and 2D NMR and high-resolution mass spectral analyses as well as comparison with the literature. Compounds 2 and 7 showed antiproliferative and antimigratory activity against the highly metastatic human prostate cancer cell line PC-3 cells without cytotoxicity. The phenanthridine alkaloid class was identified as having potential for use to control prostate cancer proliferation and migration.
Keywords: Amaryllidaceae; Pancratium maritimum; alkaloids; antimigratory; antiproliferative activity